The Combination 2,4-D and BAP to Induce Embryogenic Callus from Some Varieties of Soybean (Glycine max (L.) Merrill) on Hypoxic and In Vitro Condition - Bertryda Hastipa Manurung; Revandy Iskandar Damanik; Eva Sartini Bayu (Universitas Sumatera Utara, 2018)
The purpose of this research was to determinate the growth response of embryogenic callus from some varieties of soybean (Glycine max (L.) Merrill) on hypoxic and in vitro condition. The research was conducted at The Tissue Culture Laboratory of Agriculture Faculty in University of Sumatera Utara on April until December 2016. This research had two stages, induction of embryogenic callus and analysis metabolism of callus after hypoxic condition with t-test. This analysis used factorial Completely Randomized Design with two factors. The first factors were varieties of soybean and the second factors were combination of Plant Growth Regulator (PGR) (5 mg/l 2,4-D + 1 mg/l BAP, 10 mg/l 2,4-D + 1,5 mg/l BAP, and 15 mg/l 2,4-D + 2 mg/l BAP). The result showed the varieties, combination of PGR, and interaction of varieties and PGR give significant effect to weight callus. The result of T-test showed that in hypoxic condition, POD enzyme exercise on Gepak Kuning’s callus in 5 mg/l 2,4-D + 1 mg/l BAP was different before and after hypoxic condition. Keywords : 2,4-D, BAP, embryogenic callus, hypoxic, soybean